Bridging the gap between intention and enactment: a Bayesian analysis of pre-service teachers’ implementation of inquiry-based practical work in STEM (science-led) classrooms - Tsakeni, Maria; Mosia, Moeketsi; Egara, Felix O.; Nwafor, Stephen C. (Frontiers in Education, 2026)
IntroductionThe alignment between pre-service teachers’ instructional intentions and their actual classroom enactment remains a critical yet underexplored issue in STEM teacher education. In this study, STEM education is operationalised through science-led inquiry-based practical work that integrates scientific reasoning, mathematical thinking, and problem-solving practices characteristic of integrated STEM pedagogy. The study investigates the intention–enactment gap experienced by pre-service teachers during practicum.MethodsA cross-sectional research design was employed. Data were collected from a cohort of pre-service teachers and analysed using Bayesian statistical modelling to estimate (i) the average gap between intended and enacted inquiry-based practical work, (ii) variations across demographic subgroups, and (iii) associations with educational and programme-related factors.ResultsFindings indicate that, on average, pre-service teachers intended to implement significantly more inquiry-based practical work than they were able to enact during practicum. Age-related differences were observed, with younger pre-service teachers exhibiting larger intention–enactment gaps, while gender differences were minimal and uncertain. Participation in peer or learning communities emerged as the strongest predictor of alignment, with actively engaged pre-service teachers demonstrating substantially smaller gaps. Conversely, higher self-reported communication skills were unexpectedly associated with larger gaps, potentially reflecting heightened professional aspirations or practicum roles that limited opportunities for hands-on enactment.ConclusionThe findings highlight the complexity of translating instructional intentions into classroom practice and suggest that individual competencies alone are insufficient to bridge the intention–enactment gap. Deliberately designed, feedback-rich, and collaborative learning environments play a critical role in supporting pre-service teachers to transform pedagogical aspirations into enacted STEM practice. These results offer both theoretical insights and actionable guidance for strengthening STEM teacher preparation programmes.